Dayak Kaharingan di tengah perubahan sosial ekologi dan praktik perpindahan agama di pedesaan Kalimantan Tengah - Nindyo Budi Kumoro (LIPI Press, 2020)
This paper tries to explain the relation between social-ecological change and the phenomenon of religious conversion in a minority group in Indonesia. The case study is the Dayak community religion in Central Kalimantan, Kaharingan, with 'world' or 'official' religions such as Christianity, Catholicism, or Islam. The study of Kaharingan in this paper is placed in the context of Kalimantan as an object of resource expansion with massive intensity by the global economic capitalist chain. Forest exploitation and local gold mining activity from outsiders urged Dayaks to participate in new economic patterns, which caused swidden cultivation to become inaccessible to villagers and began to slowly be abandoned. This has implications for the transformation of the Dayaks in perceiving their relationship with the natural environment, a relationship that was previously the basis of Kaharingan religious beliefs and practices. Based on my ethnographic research in the rural Dayak community upriver Katingan, this paper shows that the religious conversion from Kaharingan to a new religion is more driven by social and economic morals that emphasize individual-household relations rather than the communal-collective pattern as before. This paper also argues that although traditional beliefs have slowly been abandoned, the practice of Kaharingan ceremonies is still held intensively for different purposes.Keywords: Minority religion, socio-economic and ecological change, religious conversion Abstrak Artikel ini berupaya menunjukkan relasi perubahan sosial-ekologi dengan fenomena perpindahan agama pada kelompok minoritas di Indonesia. Studi kasus dalam tulisan ini adalah agama masyarakat Dayak Kalimantan Tengah, yakni Kaharingan, dengan agama ‘dunia’ atau ‘resmi’ seperti Kristen, Katolik, maupun Islam di sana. Kajian mengenai Kaharingan di sini diletakkan dalam konteks Kalimantan sebagai obyek dari ekspansi sumber daya dengan intensitas yang massif oleh rantai ekonomi kapitalisme global. Eksploitasi kayu maupun pertambangan lokal dari pihak luar mendorong orang Dayak turut berpartisipasi dalam pola ekonomi baru menggeser perladangan berpindah ke posisi yang tidak menguntungkan. Hal ini turut mendorong perubahan orang Dayak dalam memaknai relasi mereka dengan alam sekitar, relasi yang sebelumnya menjadi basis kepercayaan dan praktik agama Kaharingan. Dengan mendasarkan pada hasil riset etnografi pedesaan Dayak di hulu Sungai Katingan, tulisan ini menunjukkan bahwa perpindahan agama dari Kaharingan ke agama baru lebih didorong oleh moral sosial dan ekonomi baru yang menekankan relasi individu-rumah tangga dari pada komunal-kolektif seperti sebelumnya. Tulisan ini juga ingin menunjukkan meskipun kepercayaan lama telah ditinggalkan, namun praktik upacara Kaharingan tetap digelar dengan intensif meskipun untuk tujuan yang berbeda. Kata kunci: Agama minoritas, perubahan material-ekologi, perpindahan agama